Improving The Effectiveness of Mathematics Learning Through Artificial Intelligence: Literature Review - Maulida, Laela; Nurossobah, Pipit; Aura, Billy Anggun; Nengsih, Eka Dwi; Rasilah, Rasilah (MASI Mandiri Edukasi, 2024)
Industrial Revolution 4.0 has fundamentally transformed the educational landscape. Rapid advances in technology, especially artificial intelligence (AI), demand significant curriculum adaptations. Mathematics, as the foundation of science, is the main focus in efforts to integrate AI into the learning process. This research aims to examine in depth the effect of applying AI in mathematics learning on students' learning capacity. Through a comprehensive literature study referring to various scientific journals and Google Scholar articles, this research analyzes various aspects related to the application of AI in mathematics learning. Analysis includes mapping trends in AI implementation, evaluating the effectiveness of various AI approaches, identifying factors that influence successful implementation, and exploring the positive and negative impacts of AI on the learning process. The findings of this research show that the application of AI in mathematics learning has enormous potential to increase student learning motivation, personalize learning, and deepen understanding of concepts. However, research also identifies a number of challenges, such as gaps in technology access, the need for appropriate pedagogical development, and the potential for AI to replace teachers' roles. Based on these findings, this research concludes that integrating AI in mathematics learning requires careful planning and strong collaboration between educators, technology developers, and policymakers. The implications of this research include the importance of flexible curriculum development, continuous teacher training, and the provision of adequate technological infrastructure.